Osmosis: Chewy naked egg, in or out? - Atok Miftachul Hudha; Kalim Ullah; Rani Darmayanti (CV. FOUNDAE, 2023)
The experimental method is the right way to learn biology. Osmosis is an important biological concept that can be used to understand other biology concepts and requires experimental activities so students can understand it better. The implementation of experimental activities will be guided by Student Worksheets (LKPD-Ex). The purpose of this study was to develop LKPD-Ex on osmosis experiments with chicken egg media for class XI students. This research is a development-research (RnD) using a four-D model, namely the definition phase, design phase, development phase, and deployment phase. However, it was changed to 3D because the media was developed only to test the feasibility of the E-LKPD media. Good validation results from experts score 89.08% of the assessment of material experts and media experts, and 92.63% of student responses with very decent criteria. From these data it can be concluded that the development of Experimental Student Worksheets (LKPD-Ex) on the Osmosis Experiment is very feasible to be used as an alternative in the learning process so that it can be tested in supporting the maximum learning process.